Symptom load and general function among patients with erythema migrans: a prospective study with a 1-year follow-up after antibiotic treatment in Norwegian general practice - Knut Eirik Eliassen; Reidar Hjetland; Harald Reiso; Morten Lindbæk; Hedda Tschudi-Madsen (Taylor & Francis Group, 2017)
Objective: Promptly treated erythema migrans (EM) has good prognosis. However, some patients report persistent symptoms. Do patients with EM have more symptoms than the general population? We describe individual symptoms and general function in EM-patients at time of diagnosis and one year after treatment. Design: Prospective study with 1-year follow up after treatment. Questionnaires included a modified version of the Subjective Health Complaints Inventory, comprising three additional Lyme borreliosis (LB) related symptoms. General function was assessed using a five-point scale modified from the COOP/WONCA charts. Setting: Norwegian general practice. Subjects: A total of 188 patients were included in a randomized controlled trial comparing three antibiotic regimens for EM, of whom 139 had complete data for this study. Main outcome measures: Individual symptoms, symptom load and general function. Results: Mild symptoms were common, reported by 84.9% at baseline and by 85.6% at follow-up. At baseline, patients reported a mean of 5.4 symptoms, compared with 6.2 after one year. Severely bothersome symptoms and severely impaired general function were rare. Tiredness was the most reported symptom both at baseline and at follow-up. Palsy (other than facial) was the least reported symptom, but the only one with a significant increase. However, this was not associated to the EM. Conclusion: The symptom load was comparable to that reported in the general population. We found an increase in symptom load at follow-up that did not significantly affect general function. Implication: Monitoring patients' symptom loads prior to treatment reduce the probability of attributing follow-up symptoms to LB.Key points Erythema migrans has a good prognosis.Patients treated for erythema migrans have a slight increase in symptom load one year after treatment. This increase does not affect general function. The levels of subjective health complaints in patients treated for erythema migrans are comparable to the background population.